Answer:
[tex]T_7 = 11[/tex]
[tex]T_n = 2n- 3[/tex]
Step-by-step explanation:
Given
[tex]S_n = n^2 -2n[/tex]
[tex]T_n = S_n - S_{n-1}[/tex]
Solving (a): T7
Substitute 7 for n in [tex]T_n = S_n - S_{n-1}[/tex]
[tex]T_7 = S_7 - S_{7-1}[/tex]
[tex]T_7 = S_7 - S_6[/tex]
Calculate S7 and S6
[tex]S_n = n^2 -2n[/tex]
[tex]S_7 = 7^2 - 2 * 7 = 35[/tex]
[tex]S_6 = 6^2 - 2 * 6 = 24[/tex]
So:
[tex]T_7 = 35 -24[/tex]
[tex]T_7 = 11[/tex]
Solving (b): Tn
[tex]T_n = S_n - S_{n-1}[/tex]
Where [tex]S_n = n^2 -2n[/tex]
Calculate[tex]S_{n-1}[/tex]
We have:
[tex]S_{n-1} =(n-1)^2 - 2(n-1)[/tex]
Open brackets
[tex]S_{n-1} = n^2 -2n + 1 -2n +2[/tex]
[tex]S_{n-1} = n^2 -2n-2n + 1 +2[/tex]
[tex]S_{n-1} = n^2 -4n + 3[/tex]
So:
[tex]T_n = S_n - S_{n-1}[/tex]
[tex]T_n = n^2 - 2n - (n^2 -4n + 3)[/tex]
[tex]T_n = n^2 - 2n - n^2 +4n - 3[/tex]
Collect Like Terms
[tex]T_n = n^2 - n^2- 2n +4n - 3[/tex]
[tex]T_n = 2n- 3[/tex]